Genetic variants regulating insulin receptor signalling are associated with the severity of liver damage in patients with non-alcoholic fatty liver disease. (22nd February 2010) - Dongiovanni, P; Valenti, L; Rametta, R; Daly, A K; Nobili, V; Mozzi, E; Leathart, J B S; Pietrobattista, A; Burt, A D; Maggioni, M; Fracanzani, A L; Lattuada, E; et al.
Abstract : Background/aims: The aim of this study was to assess the effect of functional ENPP1(ectoenzyme nucleotide pyrophosphate phosphodiesterase 1)/PC-1 (plasma cell antigen-1) and IRS-1 (insulin receptor substrate-1) polymorphisms influencing insulin receptor activity on liver damage in non-alcoholic fatty liver disease (NAFLD), the hepatic manifestation of the metabolic syndrome, whose progression is associated with the severity of insulin resistance. Patients and methods: 702 patients with biopsy-proven NAFLD from Italy and the UK, and 310 healthy controls. The Lys121Gln ENPP1/PC-1 and the Gly972Arg IRS-1 polymorphisms were evaluated by restriction analysis. Fibrosis was evaluated according to Kleiner. Insulin signalling activity was evaluated by measuring phosphoAKT levels by western blotting in a subset of obese non-diabetic patients. Results: The ENPP1 121Gln and IRS-1 972Arg polymorphisms were detected in 28.7% and 18.1% of patients and associated with increased body weight/dyslipidaemia and diabetes risk, respectively. The ENPP1 121Gln allele was significantly associated with increased prevalence of fibrosis stage >1 and >2, which was higher in subjects also positive for the 972Arg IRS-1 polymorphism. At multivariate analysis, the presence of the ENPP1 121Gln and IRS-1 972Arg polymorphisms was independently associated with fibrosis >1 (OR 1.55, 95% CI 1.24 to 1.97; and OR 1.57, 95% CI 1.12 to 2.23, respectively). Both polymorphisms were associated with a marked reduction of ∼70% of AKT activation status, reflecting insulin resistance and disease severity, in obese patients with NAFLD. Conclusions: The ENPP1 121Gln and IRS-1 972Arg polymorphisms affecting insulin receptor activity predispose to liver damage and decrease hepatic insulin signalling in patients with NAFLD. Defective insulin signalling may play a causal role in the progression of liver damage in NAFLD.